2016
DOI: 10.1098/rspb.2016.1948
|View full text |Cite
|
Sign up to set email alerts
|

Automatic facial mimicry in response to dynamic emotional stimuli in five-month-old infants

Abstract: Human adults automatically mimic others' emotional expressions, which is believed to contribute to sharing emotions with others. Although this behaviour appears fundamental to social reciprocity, little is known about its developmental process. Therefore, we examined whether infants show automatic facial mimicry in response to others' emotional expressions. Facial electromyographic activity over the corrugator supercilii (brow) and zygomaticus major (cheek) of four-to five-month-old infants was measured while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 58 publications
2
48
2
Order By: Relevance
“…Twenty‐three additional infants were tested but not included in the final analysis due to fussiness ( n = 11), not accepting electrodes on their face ( n = 7), or excessive movement artefacts in the signal ( n = 5). This high dropout rate is typical in EMG studies with infant and children population (Geangu et al, ; Isomura & Nakano, ). Parents were informed about the procedure and gave their written consent to their child's participation.…”
Section: Methodsmentioning
confidence: 76%
See 3 more Smart Citations
“…Twenty‐three additional infants were tested but not included in the final analysis due to fussiness ( n = 11), not accepting electrodes on their face ( n = 7), or excessive movement artefacts in the signal ( n = 5). This high dropout rate is typical in EMG studies with infant and children population (Geangu et al, ; Isomura & Nakano, ). Parents were informed about the procedure and gave their written consent to their child's participation.…”
Section: Methodsmentioning
confidence: 76%
“…Another possible limitation is the attrition rate (60% of the sample), which could question the appropriateness of our paradigm for the population tested. However, high attrition rates are common in studies with infants and children that make use of sensors to measure electromyographic (Geangu et al, ; Isomura & Nakano, ) as well as electroencephalographic responses (Stets, Stahl, & Reid, ). In our study, almost 30% of the participants were excluded due to infants not accepting the sensors on their face and to movements artefacts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Datyner et al (2017) showed similar results in 7-montholds viewing happy and angry facial expressions. Interestingly, Isomura and Nakano (2016) showed that infants aged 4-5 months showed increased corrugator EMG response to audiovisual crying and increased zygomaticus EMG response to audiovisual laughing, but no clear increase in response to unimodal emotional stimuli (faces or vocalizations individually). There is evidence that at this age, infants can discriminate happy, sad and angry emotions from bimodal audio-visual stimuli, but that sensitivity to unimodal auditory stimuli emerges at 5 months, and visual stimuli at 7 months (Flom and Bahrick, 2007).…”
Section: Evidence Of Motor Matching In Childrenmentioning
confidence: 99%